2013
DOI: 10.3346/jkms.2013.28.2.213
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Efficacy of Stereotactic Ablative Radiotherapy for Barcelona Clinic Liver Cancer-C Stage Hepatocellular Carcinoma

Abstract: The purpose of this study was to assess the feasibility and efficacy of stereotactic ablative radiotherapy (SABR) for liver tumor in patients with Barcelona Clinic Liver Cancer (BCLC)-C stage hepatocellular carcinoma (HCC). We retrospectively reviewed the medical records of 35 patients between 2003 and 2011. Vascular invasion was diagnosed in 32 patients, extrahepatic metastases in 11 and both in 8. Thirty-two patients were categorized under Child-Pugh (CP) class A and 3 patients with CP class B. The median SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 26 publications
2
43
0
Order By: Relevance
“…AEs are major issues in SBRT for locally advanced HCC. Bujold et al and Bae et al reported that SBRT-induced toxicity ≥ grade 3 was seen in 14-30% of HCCs 30,31 . In the particle radiotherapy for locally advanced HCC, the incident rate of severe toxicities was found to be low, but toxicities did occur [32][33][34] .…”
Section: Discussionmentioning
confidence: 99%
“…AEs are major issues in SBRT for locally advanced HCC. Bujold et al and Bae et al reported that SBRT-induced toxicity ≥ grade 3 was seen in 14-30% of HCCs 30,31 . In the particle radiotherapy for locally advanced HCC, the incident rate of severe toxicities was found to be low, but toxicities did occur [32][33][34] .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent reports indicated that SBRT was as effective as TACE and RFA (33,34). In a previous series, SBRT provided 1-, 2-, and 3-year local control rates of 56-100%, 53-95%, and 51-92%, and 1-, 2-, and 3-year survival rates of 32-100%, 55-100%, and 21-82% for HCC, respectively (11)(12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Sbrt For Primary Liver Cancersmentioning
confidence: 91%
“…Radiotherapy has also been used for palliative care in liver tumors (7)(8)(9). Modern radiotherapies, including stereotactic body radiation therapy (SBRT), intensity-modulated radiotherapy (IMRT), and particle therapies, have recently attracted increasing attention as therapeutic modalities for various malignancies and have dramatically increased the use of radiation therapy as a curative modality (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26).…”
Section: Abstract Surgical Resection Is the Standard Therapy Formentioning
confidence: 99%
“…The 1-and 3-year local control rates were 69% and 51%, respectively. SBRT dose of BED ≥80 Gy 10 was a significant prognostic factor for survival [25].…”
Section: Rt Fractionationmentioning
confidence: 99%